Pembuatan Bioetanol dengan Proses Fermentasi Nira Aren Menggunakan Saccharomyces Cereviceae Dengan Variasi pH Awal Dan Waktu Fermentasi - Muria, Sri Rezeki (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Bioethanol is an alternative fuel that produced from plant materials containing starch, sugar, and cellulose through a process of fermentation, and also bioethanol is environmentally friendly and renewable natural resources. Palm juice is one of potential materials to be processed into bioethanol. Availability of sugar palm land in Indonesia makes sugar palm juice has the potential to be processed into bioethanol. Fermentation process using yeast Saccharomyces cereviceae, glucose is converted into bioethanol and carbon dioxide. This research was observed the effect of variation in pH 4,5; 5,0; 5,5; 6,0 and variations of fermentation time of 24, 36, 48, 60 dan 72 hours. Fermentation took place at room temperature (25 - 30 0C) and stirring speed of 200 rpm. Ethanol concentrations were analyzed using alcoholmeter. The optimum fermentation process was shown on the pH 4,5 fermentation time of 72 hours with ethanol concentrations obtained 7% (v / v) or 55,25 mg / ml.Keyword : Bioethanol, fermentation, Palm juice, Saccharomyces cereviceae.